Case report: Mixed hydrofluoric and nitric acid mist inhalation poisoning - Zhang, Tongyue; He, Xingbing; Wang, Chen; Zhou, Zhiqiang; Genjiafu, Aerbusili; Wen, Zixin; Jian, Xiangdong; Li, Qilu (Frontiers in Medicine, 2024)
Introduction: Hydrofluoric and nitric acids are strongly acidic substances with strong oxidation and are widely used in industrial production. Chemical pneumonia caused by the inhalation of strong acids has occasionally been reported. Severe chemical pneumonia can lead to acute pulmonary edema and life-threatening acute respiratory distress syndrome. The treatment of chemical pneumonia mainly relies on symptomatic and supportive treatment such as antiinflammatory and anti-infection. Case description: This study reports three cases of chemical pneumonia caused by the inhalation of a mixed hydrofluoric and nitric acid mist during an occupational exposure accident. After appropriate emergency symptomatic treatment, such as oxygenation and excretion promotion, cough, and difficulty in breathing were alleviated but not completely cleared. Discussion: Most of the literature reports damage caused by hydrogen fluoride on the skin and mucosal burns, and reports on lung damage caused by the inhalation of large amounts of hydrogen fluoride gas are relatively rare. Usually in the early stage of this kind of patients can have elevated blood picture, hypoxemia, pulmonary CT inflammatory plaque changes, so as to have obvious respiratory irritation symptoms. When inhaling a large amount of hydrofluorine mixed nitric acid mist, in addition to considering the occurrence of severe pneumonia, we should also be alert to the occurrence of other organ damage and electrolyte disorder. Conclusion: As occupational hydrogen fluoride gas inhalation poisoning often occurs in groups, improving the safety facilities and standard operations of small-and medium-sized enterprises is necessary. For medical workers, it is necessary to be alert to the occurrence of severe toxic pneumonia and severe fluorosis.